Tourist experience: The catalyst role of tourism in comforting melancholy, or not - Christou, Prokopis A.; Simillidou, Aspasia (My University, 2020)
Although it cannot be interpreted as severe depression, melancholy has disquieted individuals and societies for millennia. This study explores the extent to which tourism can move beyond the formation of enjoyable experiences and become a source of comfort for melancholy. The present study reveals that tourism does not act as a panacea for melancholy. Nonetheless, it may substantially relieve the symptoms through a concurrent amalgam of pleasure and activity factors, distractions, and the seclusion choices it offers. The eagerness associated with an imminent leisure trip and the strength to fight challenges in the personal and social domains following a reviving travel experience are also imperative comforting dynamics. A relevant research agenda is proposed, and the managerial implications for how the tourism industry can secure comforting experiences are discussed.
Keywords: Melancholy; Depression; Tourist experience; Leisure; Happiness